Anti-tumor activities of active ingredients in Compound Kushen Injection - Wang Wei; You Rong-li; Qin Wen-jie; Hai Li-na; Fang Ming-jing; Huang Guo-hua; Kang Rui-xia; Li Ming-hua; Qiao Yu-feng; Li Jian-wei; Li An-ping (Acta Pharmacologica Sinica, 2017)
Kushen (Radix Sophorae Flavescentis) has a long history of use for the treatment of tumors, inflammation and other diseases in traditional Chinese medicine. Compound Kushen Injection (CKI) is a mixture of natural compounds extracted from Kushen and Baituling (Rhizoma Smilacis Glabrae). The main principles of CKI are matrine (MT) and oxymatrine (OMT) that exhibit a variety of pharmacological activities, including anti-inflammatory, anti-allergic, anti-viral, anti-fibrotic and cardiovascular protective effects. Recent evidence shows that these compounds also produce anti-cancer actions, such as inhibiting cancer cell proliferation, inducing cell cycle arrest, accelerating apoptosis, restraining angiogenesis, inducing cell differentiation, inhibiting cancer metastasis and invasion, reversing multidrug resistance, and preventing or reducing chemotherapy- and/or radiotherapy-induced toxicity when combined with chemotherapeutic drugs. In this review, we summarize recent progress in studying the anti-cancer activities of MT, OMT and CKI and their potential molecular targets, which provide clues and references for further study.